Introduction - Zeise-Ssa., M (Springer International Publishing, 2020)
This chapter first tries to lay the ground for this book giving definitions and characterizations of “what is psychology?" and “what is the scientific process?" Second, it intends to give reasons why a psychologist should study neuroscience by offering a description of the relationship between psychology and neuroscience. © Springer Nature Switzerland AG 2021.